Bagaimana Ketergantungan Media Sosial Memberikan Dampak pada Kesejahteraan Psikologis Karyawan - Ali Fatah; Rina Anindita (Neolectura, 2022)
This study contributes to how measure the influence of social media addiction on the welfare of non-financial employees and employee performance, and contributes to the information on how to limit the limits in playing social media, especially when at work and the adverse effects of playing social media excessively, by playing social media overly will affect productivity in doing work. Based on previous research related to the influence of social media addiction on employee well-being and employee performance, data collection in this study uses survey methods that use the dissemination of questionnaires. Data were processed from as many as 153 respondents and were selected by purposive sampling method from February to May 2021 in the DKI Jakarta-Indonesia area. This type of research is causality-quantitative using the analysis method of structural equation model (SEM) data. This study shows that the higher the level of social media addiction, it will improve the welfare of non-financial employees but have no impact on employee performance. An interesting finding in this study is that social media addiction will indirectly improve performance through non-financial well-being.